Nuclear DNA content of thirty species of neotropical fishes - Carvalho, Margarida Lima; Oliveira, Claudio [UNESP]; Foresti, Fausto [UNESP] (FapUNIFESP (SciELO), 1998)
The present paper reports nuclear DNA content in 30 Neotropical freshwater fish species and summarizes the data on other Neotropical species presented in the literature. Among Neotropical fishes, the nuclear DNA content ranges from 1.04 ± 0.09 pg/nucleus in Corydoras cf. simulatus (2n = 62) to 248.0 pg/nucleus in Lepidosiren paradoxa (2n = 38). A general analysis of the data obtained in the present study for each species showed that DNA measurements were practically constant at the individual level, while significant differences were observed among individuals of the same population. This observation was valid for all species analyzed and was more evident in those species that presented other karyotypic particularities such as sex chromosomes or supernumerary chromosomes. The importance of changes in nuclear DNA content in the evolutionary process of Neotropical fishes is discussed.
Keywords: cell nucleus DNA; animal cell; cytogenetics; diploidy; DNA determination; fish; karyotype; molecular evolution; nonhuman; sex chromosome; supernumerary chromosome; Animalia; Corydoras; Lepidosiren paradoxa; Pisces